Brown-Vialetto-Van Laere Syndrome as a Mimic of Neuroimmune Disorders: 3 Cases From the Clinic and Review of the Literature. (May 2017) - Allison, Tyler; Roncero, Inés; Forsyth, Rob; Coffman, Keith; Pichon, Jean-Baptiste Le
We present 3 patients identified at 2 different institutions with Brown-Vialetto-Van Laere syndrome. Each patient was initially diagnosed with a neuroimmune disorder for a period of a few weeks to a few months. In each case, genetic analysis revealed mutations in one of the riboflavin transporters, confirming Brown-Vialetto-Van Laere syndrome. It is likely that Brown-Vialetto-Van Laere syndrome is more common than previously reported, and because it mimics neuroimmune disorders, it may be misdiagnosed as such. It shares many features with diseases such as chronic inflammatory demyelinating neuropathy, may present with positive cerebrospinal fluid antibody titers, and may transiently respond to intravenous immunoglobulin. We review the literature on Brown-Vialetto-Van Laere syndrome and Fazio-Londe syndrome, 2 riboflavin transporter disorders, looking for clinical presentations that may lead to confusion with neuroimmune disorders. We emphasize the importance of correctly diagnosing the disease, as its treatment is relatively benign and will stop progression of the disease and may even reverse it.